2019
DOI: 10.1186/s13550-019-0584-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of myocardial 99mTc-labeled bisphosphonate uptake with cadmium zinc telluride camera in patients with transthyretin-related cardiac amyloidosis

Abstract: Purpose We aimed to compare different methods for semi-quantitative analysis of cardiac retention of bone tracers in patients with cardiac transthyretin amyloidosis (ATTR). Methods Data from 67 patients with ATTR who underwent both conventional whole-body scan and a CZT myocardial SPECT (DSPECT, Spectrum Dynamics) 3 h after injection of 99mTc-labeled bone tracer were analyzed. Visual scoring of cardiac retention was performed on whole-body scan according to Perugini 4-point grading system from 0 (no uptake) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Novel therapeutic agents recently introduced may require precise assessment of disease burden at diagnosis and during follow up [ 1 , 17 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel therapeutic agents recently introduced may require precise assessment of disease burden at diagnosis and during follow up [ 1 , 17 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Feasibility of quantitative SPECT/CT with Tc-DPD/HDP/PYP in patients with suspected ATTR was recently assessed using CZT-based SPECT/CT scanners [ 19 21 ] with overall similar results to conventional SPECT/CT. Bone activity showed no significant differences between the scores, whereas lung and soft tissue activity was significantly higher in grade 2 and 3 [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Amyloid bone scan agents imaging has already been attempted using CZT camera. 14,15 However, the majority of these studies used the H/CL method originally introduced by Bokuhari. 11 The value of SUV, which was used in the present study, was originally developed for use in FDG PET in oncology.…”
Section: Why Are More Precise Measurements Needed?mentioning
confidence: 99%
“…Masri et al showed comparable diagnostic performance in 233 patients who had planar and SPECT imaging at 1 h and 3 h. 17 For planar images grades 1-2, SPECT was needed to make the diagnosis. SPECT/CT enables quantitation 19,20 and localization of uptake in soft tissue. 21,22 Another variation of the protocol is timing of the imaging, from 10 min as suggested by Santarelli et al in this issue, 4 to 3 h after the injection, the most validated time point.…”
Section: Imaging Protocols-the More the Merrier!mentioning
confidence: 99%